Halal Product Assurance as Legal Protection for Muslim Consumers in Indonesia - Masri, Esther; Irianto, Sigit; Masriani, Yulies Tiena; Falah, Syauqi Muhammad Shobibul (Al-Ahkam, 2025)
This research is motivated by the still-weak legal protection for Muslim consumers in Indonesia concerning the circulation of products without clear halal certification, despite existing regulations such as Law Number 33 of 2014 on Halal Product Assurance. This study aims to analyze the implementation of halal product assurance and its effectiveness in providing legal protection for consumers and formulate strategies for strengthening the existing regulatory framework. This research uses a normative juridical method combined with an empirical approach through field interviews with business actors, relevant authorities, and consumers to obtain firsthand data. The findings indicate that while the legal framework is adequate, its implementation faces several challenges, including limited infrastructure, a lack of understanding among micro, small, and medium enterprises (MSMEs), and weak law enforcement. Based on these findings, the study recommends strengthening the sanctions stipulated in Article 56 of the Halal Product Assurance Law, increasing the capacity of halal inspection and auditing institutions, and enhancing inter-agency collaboration to ensure that all circulated products are halal-certified, thereby providing stronger legal protection for Muslim consumers.